Obremenitveno testiranje pri osebah z okvaro hrbtenjače - Žen Jurančič, Marijana (Rehabilitacija (Ljubljana), 2012)
Exercise testing is a frequently used diagnostic procedure in the field of cardio-pulmonary diseases. The test is standardized, but performance in persons with spinal cord injury has some specifics. Because of their limitations of muscular, pulmonary and autonomic function, the preparation before the test, the performance and the interpretation of the results are different. Functional capacity in persons with spinal cord injury is low compared to the general population. This leads to higher incidence of cardiovascular diseases.
Keywords: autonomic dysfunction; avtonomna disfunkcija; Exercise Test; mišična disfunkcija; muscular dysfunction; obremenitveno testiranje; okvare hrbtenjače; pljučna disfunkcija; pulmonary dysfunction; Spinal Cord Injuries